Further Results on Graceful Antimagic Graphs - SHawkat, Noor Khalil; Ahmed, Mohammed Ali (Iraqi Journal of Science, 2023)
Graceful labeling of a graph with q edges is assigned the labels for its vertices by some integers from the set such that no two vertices received the same label, where each edge is assigned the absolute value of the difference between the labels of its end vertices and the resulting edge labeling running from 1 to inclusive. An edge labeling of a graph G is called vertex anntimagic, if all vertex weights are pairwise distinct, where the vertex weight of a vertex under an edge labeling is the sum of the label of all edges incident with that vertex. In this paper, we address the problem of finding graceful antimagic labelin for split of the star graph , graph, graph, jellyfish graph , Dragon graph , kite graph ( and the double comb graph ,